Pre-Engraftment Syndrome after Double Unit Cord Blood Transplantation: a Distinct Syndrome not Associated with Acute Graft-Versus-Host Disease - Patel, Kevin J. (2009)
The pre-engraftment syndrome (PES) after cord blood (CB) transplantation (CBT) is poorly characterized. Therefore, we reviewed 52 consecutive double unit CBT recipients treated for high-risk hematological malignancies. PES was defined as unexplained fever >38.3°C (101F) not associated with infection and unresponsive to antimicrobials, and/or unexplained rash occurring before or at neutrophil recovery. CBT recipients (median 38 years, range 3-66) received either myeloablative (n=36) or non-myeloablative (n=16) conditioning. Sixteen patients (31%) fulfilled PES criteria: 15 with fever [onset median 39°C (102.2F)] with 13 also having rash, and one with rash alone. The median onset was 9 days (range 5-12) post-transplant (a median of 14 days before neutrophil recovery). Sixteen patients received IV methylprednisolone (MP) (14 PES, 2 with infection and possible PES; median dose 1 mg/kg, median duration 3 days) with 15/16 (94%) having fever resolution in ≤24 hours. Recurrent PES (n=3) resolved with retreatment. There was no association between the development of PES and the likelihood of sustained donor engraftment, the speed of neutrophil recovery, grade II-IV acute graft-versus-host disease (aGVHD), day 180 transplant-related mortality, or survival. PES is common after CBT, precedes neutrophil recovery, is distinct from and does not predict for aGVHD, and responds promptly to short course corticosteroids.